The Profile of XI Grade Students’ Scientific Thinking Abilities on Scientific Approach Implementation - Suciati, S.; Ali, M. N.; Anggraini, A. F.; Dermawan, Z. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2018)
This study aimed at analyzing XI grade studentsÃ¢â‚¬â„¢ scientific thinking abilities on the implementation of the scientific approach.Ã‚Â 82 students of XI grade science class at three state senior high schools in Surakarta involved in this study. The studentsÃ¢â‚¬â„¢ scientific thinking abilities illustrated as the studentsÃ¢â‚¬â„¢ competence in seven aspects: the purpose of science; science question, science information, science interpretation, science concept, science assumption, science implication (Paul & Elder, 2003). The data on studentsÃ¢â‚¬â„¢ scientific thinking abilities were collected using essay test on worksheet and interview methods. The instrument had been validated by expert judgement and students as a user. The scores were used to represent the studentsÃ¢â‚¬â„¢ scientific thinking abilities in three categories (low, middle,high).Ã‚Â The results of the study showed that studentsÃ¢â‚¬â„¢ competence in seven aspects of scientific thinking abilities: purpose of science (62,00%); science question (36,6%), science information (39,66%), science interpretation (41,00%), science concept (43,33), science assumption (38,33%), science implication (21,33%). Therefore, it concluded that the XI grade studentsÃ¢â‚¬â„¢ scientific thinking abilities on the implementation of scientific approach was at the low category. It was suggested that the learning model based scientific approach be conducted for the studentsÃ¢â‚¬â„¢ scientific thinking abilities improvement.